Statistical analysis of global properties of galaxies in the direction of the Fornax cluster with S-PLUS - Calderón, Juan Pablo (2021)
In the context of the S-PLUS Fornax Project (S+FP), we analyze the galaxy population in the direction of the Fornax cluster ($D≈ 20$~Mpc). We have 23 fields of size $1.4^{°}× 1.4^{°}$, covering the projected positions of 999 Fornax galaxies reported in the literature. 244 of those galaxies are detected with confident photometry in our fields which were observed simultaneously in 12 photometric bands. Besides those of Fornax galaxies, we obtained confident structural and photometric parameters for $≈ 3×10^5$ additional galaxies detected in our fields. In this work we present preliminary results on the characterization of the galaxy population of the Fornax cluster with respect to the background galaxy population. Among other goals, we expect that such a characterization provides photometric criteria to identify new candidate members of the cluster.